Analisis Pengaruh Harga, Kualitas Produk, dan Kualitas Pelayanan terhadap Keputusan Pembelian Produk pada PT. Multi Usaha Semarang - Bagus Kusuma Ardi; Yulianita Wirasaputra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of price, product quality and service quality on purchasing decisions. The population in this study was 400 people. The sample in this study was 80 using the Slovin formula. The sampling method used in this research was accidental sampling. The analysis method used is multiple linear. Hypothesis testing uses a 5% degree of freedom. The results of the reliability and validity tests show that all question items are reliable and the constructs are valid, besides that the regression meets the model fit. Hypothesis testing showed that price (X1) had a significant positive effect on purchasing decisions(Y), so hypothesis 1 was accepted. Product quality(X2) has a significant positive effect on purchasing decisions(Y), so hypothesis 2 is accepted. Service quality(X3) has a significant positive effect on purchasing decisions(Y), so hypothesis 3 is accepted.